The Relationship Between Influencer Engagement in Improving Marketing Performance Through Instagram Social Media as Mediating Variable Â - Surjono, Welly (Almana : Jurnal Manajemen dan Bisnis, 2024)
Influencer engagement through Instagram social media is becoming increasingly popular as a marketing strategy by MSMEs.This study aims to analyze the relationship between influencer engagement in improving marketing performance, with Instagram social media as a mediating variable. Influencer engagement has become an effective marketing strategy for many companies, especially in the context of MSMEs. This study uses a quantitative survey method involving respondents consisting of 125 MSME actors. Data processing was carried out using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) to test the hypothesis regarding the effect of influencer engagement on marketing performance through interactions on Instagram social media. The results showed that influencer engagement significantly affects marketing performance, directly and indirectly through Instagram social media as a mediating variable. This finding emphasizes the importance of collaboration with influencers and optimizing the use of Instagram social media to increase brand awareness, engagement, and ultimately, sales.